Effect of Daily Intake of Green Tea Catechins on Cognitive Function in Middle-Aged and Older Subjects: A Randomized, Placebo-Controlled Study - Baba, Yoshitake; Inagaki, Shun; Nakagawa, Sae; Kaneko, Toshiyuki; Kobayashi, Makoto; Takihara, Takanobu (Molecules (Basel, Switzerland), 2020)
Epidemiological studies in Japan, including the Nakajima study and the Tsurugaya study, have indicated that green tea consumption may improve cognitive impairment. Catechins, which are typical polyphenols contained in green tea, have been reported to have antioxidative, anti-inflammatory, and neuroprotective effects. However, their impact on human cognitive function remains unclear. Therefore, we performed a double-blind, randomized, controlled study to investigate the effect of 336.4 mg of decaffeinated green tea catechins (GTC) on cognitive function after a single dose and after 12 weeks of daily intake. This study included Japanese adults between the ages of 50 and 69 years with a Mini-Mental State Examination Japanese version score of >24 and self-assessed cognitive decline. The Cognitrax testing battery was used to evaluate cognitive function. The incorrect response rate on the Continuous Performance Test significantly decreased after a single dose of GTC. After 12 weeks of daily GTC intake, the response time for Part 4 of the 4-part Continuous Performance Test, which is a two-back test, was shortened. These results suggest that daily intake of GTC might have beneficial effects on working memory.